2014
DOI: 10.1111/cmi.12262
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an endocytic signal essential for the antiviral action of IFITM3

Abstract: Members of the interferon-induced transmembrane (IFITM) protein family inhibit the entry of a wide range of viruses. Viruses often exploit the endocytosis pathways to invade host cells and escape from the endocytic vesicles often in response to low pH. Localization to these endocytic vesicles is essential for IFITM3 to interfere with the cytosolic entry of pH-dependent viruses. However, the nature of the sorting signal that targets IFITM3 to these vesicles is poorly defined. In this study, we report that IFITM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
172
2
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(185 citation statements)
references
References 41 publications
8
172
2
2
Order By: Relevance
“…We found IFITM3 to be more potent than IFITM1 in its inhibition of Zika virus replication. Consistent with this, the loss of a specific endocytosis motif required for the proper localization of IFITM3 is necessary for maximal viral restriction (Jia et al, 2014;John et al, 2013). We also revealed that Zika virus causes a cytopathic effect in HeLa cells and that IFITM3 modulates this phenotype.…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…We found IFITM3 to be more potent than IFITM1 in its inhibition of Zika virus replication. Consistent with this, the loss of a specific endocytosis motif required for the proper localization of IFITM3 is necessary for maximal viral restriction (Jia et al, 2014;John et al, 2013). We also revealed that Zika virus causes a cytopathic effect in HeLa cells and that IFITM3 modulates this phenotype.…”
Section: Introductionsupporting
confidence: 81%
“…In keeping with these observations, overexpressed IFITM1 did inhibit Zika virus replication (MR766 and FSS13025 strains), but to a lesser extent than IFITM3, with the caveat that we cannot compare the levels of these two untagged proteins directly (Figures 2A-2C). An IFITM3 mutant, Y20A, which harbors a mutation in a clathrin-mediated endocytosis motif required for proper protein localization in the endosomal pathway, also demonstrated a moderately reduced ability to block viral replication (Jia et al, 2014;John et al, 2013).…”
Section: Ifitm1 Inhibits Zika Virus Replication and The Proper Localmentioning
confidence: 99%
“…5, 7 Obstructing the endocytosis of IFITM3 protein reduces its ability to inhibit influenza virus infection. 30 The rs12252 minor C allele creates a predicted splice site that would generate a putative, truncated IFITM3 transcript lacking the first 21 N-terminal amino acids (Δ1-21 variant), 3 including the Y20 amino acid, located in a motif that is recognized and bound by the AP-2 complex leading to trafficking of IFITM3 protein to endosomes and lysosomes. 30 The Δ1-21 variant protein was shown to accumulate at the plasma membrane rather than at endosomal membranes and to have reduced activity to restrict influenza virus infection in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…There is an endocytic signal in IFITM proteins responsible for antiviral activity (51). Interestingly, prolonged passage of HIV in IFITM-expressing T lymphocytes leads to emergence of Env mutants that overcome IFITM restriction.…”
Section: Figmentioning
confidence: 99%